2013
DOI: 10.1038/nn.3305
|View full text |Cite|
|
Sign up to set email alerts
|

The organization of two new cortical interneuronal circuits

Abstract: Deciphering interneuronal circuitry is central to understanding brain functions yet remains as a challenging task in neurobiology. Using simultaneous quadruple-octuple in vitro and dual in vivo whole-cell recordings, we found two previously unknown interneuronal circuits that link cortical layer 1–3 (L1-3) interneurons and L5 pyramidal neurons in the rat neocortex. L1 single-bouquet cells (SBCs) preferentially form unidirectional inhibitory connections on L2/3 interneurons that inhibit the entire dendritic-som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
359
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(391 citation statements)
references
References 60 publications
19
359
0
Order By: Relevance
“…Third, the interneurons might exert a more sophisticated control on the principal neurons output through a variety of synapses rather than a simply direct inhibition of principal neurons. Recently, there have been several studies demonstrating the importance of interneuroninterneuron interactions in the processing of cortical functions (Jiang et al 2013;Pfeffer et al 2013;Pi et al 2013;Xu et al 2013). These interactions, which consist of inhibition of inhibitory neurons, can lead to disinhibition of pyramidal cell activity by decreasing the net inhibitory drive on these neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the interneurons might exert a more sophisticated control on the principal neurons output through a variety of synapses rather than a simply direct inhibition of principal neurons. Recently, there have been several studies demonstrating the importance of interneuroninterneuron interactions in the processing of cortical functions (Jiang et al 2013;Pfeffer et al 2013;Pi et al 2013;Xu et al 2013). These interactions, which consist of inhibition of inhibitory neurons, can lead to disinhibition of pyramidal cell activity by decreasing the net inhibitory drive on these neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Although the distance between the inhibitory synapses and the soma renders a direct influence on somatic action potential generation improbable, it has been shown that activity in inhibitory interneurons in layers 2 and 3 can suppress the initiation of dendritic calcium spikes in pyramidal neurons both in vitro and in vivo. 38,52 This mechanism appears to be quite potent, as a single action potential in an interneuron can abolish dendritic calcium spikes in postsynaptic pyramidal cells ( fig. 5).…”
Section: The Effects Of General Anesthetics On Apical Dendrites Of Pymentioning
confidence: 99%
“…Specifically, a short-lasting dendritic inhibition component (up to 150 ms) is mediated by GABA type A (GABA A ) receptors, whereas a long-lasting component (up to 400 ms) relies on GABA type B (GABA B ) receptors. 52,53 Fourth, it is interesting to note that one of the main differences between basal and apical dendrites of pyramidal cells is the abundant presence, in the latter, of the hyperpolarization-activated current I h . 54,55 I h is a leak conductance that attenuates the propagation of synaptic potentials.…”
Section: The Effects Of General Anesthetics On Apical Dendrites Of Pymentioning
confidence: 99%
“…Each electrode can also be used to locally stimulate [4,[16][17][18]. Simultaneous recordings of multiple neurons are tedious to realize by patch-clamp, and the cells are only viable for a short time [19,20]. Optical and optogenetic methods provide multi-unit recording and stimulation over extended times, yet still have limited temporal resolution, and it is difficult to detect or to stimulate single action potentials (APs) in individual cells due to stray light and light scattering [3,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%